Integrative action research on using social media marketing to increase the number of enrollees and integrating the enrollment system on the website to improve the enrollment system of Rainbow Joy Learning Center, Inc. - Teodoro, Lanz Angela D. (Animo Repository, 2022)
This insider action research aimed to increase the number of enrollees at Rainbow Joy Learning Center and to improve its enrollment process. As our team implemented interventions in both cycles, we used the AIDA model and the System Development Lifecycle model. In cycle 1, my collaborators and I addressed the issue of low number of enrollees. Our objective was to increase our enrollees by using social media marketing. This cycle was a success; after implementing the intervention for three months, we gained an additional 19 enrollees. In cycle 2, my collaborators and I addressed the inefficiency of the enrollment process. Our objective was to improve the process by automating the system. My collaborators and I hired an IT team that developed the center’s website, in which the enrollment system was integrated. This cycle was a success; both parents and administrators find the automated process efficient and easy to use. As a result of my learning from the two cycles, I proposed a new AIDA model, that had been created by E. St. Elmo Lewins (1898), by making the social media marketing strategies tailored-fit for schools and learning center.